(untitled) (Research, Society and Development, 2022)
Here, we evaluated the short-term effects of Lisbon’s recently implemented green corridors (GCs) network, focusing on biological connectivity, the population’s access to spaces with different functions and to different degrees of ’clean’ mobility, and the increase in GCs’ vegetation area. The three GCs that connect more green spaces, are longer and link neighboring municipalities (Oriental, Ribeirinho and Periférico) promote greater biological connectivity. The overwhelming majority of the population (98%) benefits from low, medium and high ’clean’ mobility, and 70% of the population benefits from multifunctional GCs (i.e., in addition to the ecological function, they perform cultural and/or recreational functions). Although we expected an increase GCs’ vegetation area between 2010 and 2020, we observed the opposite: 3.30 km2 in 2010, and 2.22 km2 in 2020. However, the GCs’ vegetation area is expected to increase in the coming years as the vegetation grows and the GCs’ incompleted sections are finalized. Therefore, and if there is an increase in native species, Lisbon’s GCs network will favor both social inclusion and human well-being, as well as ecological functionality and resilience in the near future.